A study on the relationship between leadership styles and employee commitment in MASkargo Sdn Bhd / Norhaina Muhamad Torsiman - Muhamad Torsiman, Norhaina (Faculty of Business and Management, 2009)
Many people today are seeking to understand and many people are writing about the concept and practices of leadership. There are a great many reasons for the popularity of the topic, including that organizations are faced with changes like never before. This mis a study on one company that is MASkargo or Malaysia Airlines Kargo (Malaysia Airlines Cargo Sdn. Bhd.) is a cargo airline based at Advanced Cargo Centre (ACC) Kuala Lumpur International Airport (KUL) Sepang, Selangor, Malaysia. Its problem is their employees have low committed with their work. This is study on the relationship between leadership style and employee commitment. This study also using sample size of 40 respondents and choose non-probability as sampling technique. Furthermore, this studies also using primary and secondary data. Findings are interpreted using frequency and percent, descriptive statistics and also correlation. Finally, there are some conclusions and some recommendation for future research. This study shows that there is a relationship between leadership styles and employee commitment in MASkargo. Based on the findings, most of the leader or supervisor using transformational and laissez-faire leadership styles in order to treat their followers or employees. Moreover, there is a significant relationship between transformational leadership styles and employee commitment. Similar to transactional leadership style that has significant relationship but weak relationship. As a recommendation MASkargo should practice transformational leadership style rather than laissez-faire leadership style.